2005
DOI: 10.1128/mcb.25.4.1437-1445.2005
|View full text |Cite
|
Sign up to set email alerts
|

Normal Immune System Development in Mice Lacking the Deltex-1 RING Finger Domain

Abstract: The Notch signaling pathway controls several cell fate decisions during lymphocyte development, from T-cell lineage commitment to the peripheral differentiation of B and T lymphocytes. Deltex-1 is a RING finger ubiquitin ligase which is conserved from Drosophila to humans and has been proposed to be a regulator of Notch signaling. Its pattern of lymphoid expression as well as gain-of-function experiments suggest that Deltex-1 regulates both B-cell lineage and splenic marginal-zone B-cell commitment. Deltex-1 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
21
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 53 publications
2
21
1
Order By: Relevance
“…In initial studies, we examined mice that were deficient in only Deltex1, and we were unable to detect any defects in thymocyte maturation in these mice. Our results are consistent with those published by Storck et al (74) and extend their findings in several ways. First, we targeted the first coding exon of Deltex1, to be certain that Deltex1 expression is completely eliminated.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In initial studies, we examined mice that were deficient in only Deltex1, and we were unable to detect any defects in thymocyte maturation in these mice. Our results are consistent with those published by Storck et al (74) and extend their findings in several ways. First, we targeted the first coding exon of Deltex1, to be certain that Deltex1 expression is completely eliminated.…”
Section: Discussionsupporting
confidence: 94%
“…Deltex mutants share some of the phenotypic characteristics resulting from mutations in key components of the Notch pathway and exacerbate Notch loss-of-function phenotypes (23). Three mammalian homologues of the Drosophila Deltex gene have now been identified (37,74) (the Deltex1, Deltex2, and Deltex4 genes), which code for a family of cytoplasmic proteins that contain three structural domains. Domain I contains two WWE repeats (6) that have been shown to physically interact with the Notch ankyrin domains (16,50,84).…”
mentioning
confidence: 99%
“…30 Deltex1 partially inhibits the transactivation of an RBP-J-dependent luciferase reporter by NotchIC in several human and murine cells, including B (BJAP) and T (Jurkat) cells. However, a recent report 38 showed that the numbers of ectopic B cells in the thymus remained unchanged and B-cell development in the spleen was unaltered in Deltex1 mutant mice. Hence, conclusions of in vivo organ culture and biochemical studies by Izon et al 30 are still controversial.…”
Section: Discussionmentioning
confidence: 95%
“…In a previous screen for genes differentially expressed in B cells undergoing immunoglobulin hypermutation, two genes have emerged as interesting candidates: the RING finger ubiquitin ligase Deltex-1, and KLHL6 (9). A role for Deltex-1 in the immune system has recently been excluded based on a detailed analysis of Deltex-1-deficient mice (27). With regard to KLHL6, expression of this gene in lymphoid tissues (9), specifically in all stages of B-cell development (Fig.…”
Section: Discussionmentioning
confidence: 99%